Identification of Swelling Potential in Low-Plasticity Clay Soil Using the Free Swell Index Method - Yunus, Ilham; Zulfadli Ibrahim; Humairah Annisa; Indah Nur Afiah; Mentari S. Sitorus (Universitas Muslim Indonesia, 2026)
Expansive behavior of clay soil poses potential risks to geotechnical structures due to volume changes caused by water absorption. Although low plasticity clay (CL) generally exhibits lower swelling potential than highly plastic clay, its swelling characteristics still require evaluation. This study investigates the swelling potential of low plasticity clay using the Free Swell Index (FSI) method. The clay soil sample was obtained from an embankment material of a road project along the Tello River, Makassar. Basic physical properties were determined through laboratory testing, including grain size distribution and Atterberg limits, to classify the soil based on the Unified Soil Classification System (USCS). The FSI test was conducted by comparing soil volume changes in distilled water and kerosene. The results indicate that the soil is classified as CL with a plasticity index of 16% and a liquid limit of 38%. The measured FSI values range from 19% to 52.5%, with most samples exhibiting very low to low swelling potential, and only one sample showing moderate swelling. These findings confirm that low plasticity clay has limited swelling potential and that FSI is one of effective method for determining swelling behavior in CL soils for geotechnical applications.